Pineapple pests and disorders - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Pineapple pest and disorders edited by Roger Broadley, Rudolph Wassmann and Eric Sinclair 1993 63pp ISBN 0 7242 3945 6 Pbk Queensland Department of Primary Industries, GPO Box 46 Brisbane Q 4001 AUSTRALIA